2007
DOI: 10.1007/s10508-007-9200-5
|View full text |Cite
|
Sign up to set email alerts
|

Big and Beautiful: Attractiveness and Health Ratings of the Female Body by Male “Fat Admirers”

Abstract: This study examined the body weight and waist-to-hip ratio (WHR) preferences of "fat admirers" (FAs), that is, individuals who are sexually attracted to heavier partners. Fifty-six heterosexual men involved in the FA community rated a series of line drawings that varied in three levels of body weight and six of WHR for physical attractiveness and health. The results showed significant main effects of body weight and WHR, as well as a significant body weight x WHR interaction for both health ratings. In general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Feeders and Feedees sometimes connect via personal ads and form relationships with each other in real life. However, involvement in Feederism is predominately limited to the internet (Giovanelli & Peluso, 2006;Ludwig, 2008;Swami & Furnham, 2009). Individuals communicate through chat rooms and message boards on group websites such as FantasyFeeder.com and DimensionsMagazine.com.…”
Section: Introductionmentioning
confidence: 99%
“…Feeders and Feedees sometimes connect via personal ads and form relationships with each other in real life. However, involvement in Feederism is predominately limited to the internet (Giovanelli & Peluso, 2006;Ludwig, 2008;Swami & Furnham, 2009). Individuals communicate through chat rooms and message boards on group websites such as FantasyFeeder.com and DimensionsMagazine.com.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of multiple interests within specific non-normative sexual interests is well-documented in the literature. For example, research into fat admiration has suggested a distinction between "feeder" and "feedee" and has presented different body preferences within these interests (Swami & Furnham, 2009;Swami & Tovée, 2009;Terry & Vasey, 2011). However, while Aggrawal (2009bAggrawal ( , 2011 has suggested that paraphilic interests such as zoophilia and necrophilia can be classified into ten types that move from low-intensity to high-intensity interests, the "severity" of interests was not constructed thematically from participant accounts in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…For example, sociological studies have examined the roles of 4 different types of websites in the zoophilic community (Jenkins & Thomas, 2004) and have theorized four different ways in which those with zoophilic preferences may justify their preference online (Maratea, 2011). Experimental studies have examined different BMI and waist-to-hip ratio preferences in the female fat admiration community (Swami & Furnham, 2009;Swami & Tovée, 2009). Finally, forensic medical research has examined secondary sources pertaining to medical and legal cases in order to suggest a ten-point classification system for zoophilia and necrophilia, based on "severity" of interest (Aggrawal 2009b;.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Swami et al (Swami & Furnham, 2009;Swami & Tovee, 2006;2009) have recruited fat admirers for a number of their studies on body size and attractiveness by seeking out those who frequent fat admiration online dating sites. As Swami and Furnham (2009) UK, Loving It Large). They also noted (that online) it is possible to find photographs of extremely overweight and obese women and men in specialist erotica (e.g., pornographic magazines like Voluptuous and XL Girls).…”
Section: Data Collection Via Online Questionnairesmentioning
confidence: 99%